Analisis Faktor-Faktor Penentu yang Mempengaruhi Jumlah Penduduk Miskin Regional di Indonesia - Unggul Priyadi; Jati Asmoro (Unisia, 2011)
This research investigate the socio-economic variables influencing the regional poverty in indonesia. Using secondary data collected from the Central Bureau of Statistics, the independent variabels used in this reserach are regional income perkapita, income disparity, regional human development index and life expectation ratio. This research uses a pooled data analysis, i.e. random effect regression. The result of this research shows us that Human Development Index (HDI) and life expectation ratio are statisticaily effect the level of regional poverty in indonesia.Keywords: Poverty, pooled data, HDI, random effect